The Role of Tree Domestication in Green Market Product Value Chain Development in Africa - Van Damme, Patrick (Afrika Focus, 2019)
Internationally, there is increasing interest in acquiring ‘green’ market, organic and/or fair trade products, also sourced from the wild. The latter is expected to come from well-managed (forest) systems. This has led to the development and implementation of programmes designed to reduce deforestation and forest degradation (for mitigation of climate change, and sustainable provision of environmental goods and services) (REDD and REDD+). Crucially, this approach needs to be extended to the many poor, hungry and marginalized smallholder farmers in developing countries so that they can benefit from this increased market interest, but also to allow them to improve their natural resource (management) basis. In this context, agroforestry tree domestication has made considerable progress in the last 20 years, especially in Africa, in providing planting materials of many new tree crops for food, cosmetic and pharmaceutical industries and consumer markets across many agro-ecological zones. Tree domestication is an important element and the first necessary step in the development of sustainable tree production for introduction in agroforestry systems. These trees can then form the basis of Non-Timber Forest Production (NTFP) that can feed into livelihood development. In contrast to wild trees, planted trees can offer a more regular and continuous supply of NTFPs that then feed into local-to-global value chains and highly sophisticated markets that demand higher quality and greater uniformity. Together with research institutes, local farmers are now developing new, more performant cultivars of species of interest. They thus eventually help to create direct benefits from the processing and subsequent marketing of food and non-food products in local, regional and international markets. The latter activities also create business and employment opportunities in local cottage industries. Similarly, through the indirect environmental and ecological services provided by trees, food security can be greatly enhanced as agroforestry may improve the production environment of crops and thus close the yield gap (i.e. the difference between the potential and actual yield) of modern crop varieties. In this way, agroforestry adds income generation to agro-ecological approaches which together reverse the cycle of land degradation and social deprivation whilst at the same time transforming the lives of poor farmers. However, these benefits do not come without some risks: the loss of genetic diversity and local rights over genetic resources, and exploitation by unscrupulous entrepreneurs. Agroforestry developments should therefore focus on better access to ‘green’ business opportunities for poor smallholder farmers in Africa by maximizing the benefits and minimizing the risks. KEYWORDS: AGROFORESTRY TREE PRODUCTS; GENETIC DIVERSITY; INDIGENOUS TREE SPECIES; LIVELIHOODS, REDD+